A study on anxiety and depression symptoms among menopausal women: a web based cross sectional survey - Geetha Kandasamy; Dalia Almaghaslah; Mona Almanasef (Frontiers in Public Health)
BackgroundAn essential part of aging is menopause, which indicates the final phase of the female reproductive cycle. The objective of this research was to assess anxiety and depressive symptoms among menopausal women in Asir region, Saudi Arabia.MethodsThe cross-sectional survey was carried out in February to June 2024, using a random sampling procedure, study participants were selected. All menopausal women including <50 and ≥60 years old, were included, and symptoms of depression and anxiety were collected using Patient Health Questionnaire-9 (PHQ-9) Generalized Anxiety Disorder-7 (GAD-7) respectively.ResultsOf the 396 menopausal women, the majority 170 (42.9%) were <50 years old and 92 (23.2%) were between 50 and 54 years old. Two hundred eighty-one were married (71%) and 273 (68.9%) were literate. Most of them, 229 (57.8%) got married at <18 years and 196 (49.5%) have a parity of 3–5 and 189 (47.7%) women attained menopause at <50 years old. In terms of menopausal symptoms, 268 (67.7%) women experienced hot flushes; 252 (63.6%) had night sweats and were more irritable 256 (64.6%) followed by 244 (61.6%) had decreased sexual desire. In general, 258 (65.2%) and 206 (52.02%) menopausal women reported having depression and anxiety symptoms, respectively. Married (OR = 0.317; 95% CI = 0.182–0.551, p = 0.000) and literate (OR = 0.518; 95% CI = 0.309–0.868, p = 0.013) are less likely to be in depression compared to widowed/separated individuals. Literates (OR = 0.271; 95% CI = 0.165–0.443, p = 0.000), are less likely to have anxiety compared to illiterates.ConclusionThe study found that a significant percentage of menopausal women had depression and anxiety symptoms. These results emphasize the significance of screening and assessing women experiencing anxiety and depression symptoms throughout the menopausal transition. To alleviate menopausal symptoms, it is also suggested to conduct activities to educate menopausal women, such as a health awareness program in shopping centers and other public places, etc.